2006
DOI: 10.1007/s10832-006-6006-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and sintering properties of (La0.8Ca0.2−x Sr x )CrO3 perovskite materials for SOFC interconnect

Abstract: Synthesis and sintering properties of the (La 0.8 Ca 0.2−x Sr x )CrO 3 samples doped by two alkaline earth metals in comparison to the doped only by one alkaline earth metal were evaluated by phase analysis, sintering properties, thermal expansion behaviors, and electrical conductivity. The sintered (La 0.8 Ca 0.2−x Sr x )CrO 3 (x = 0, 0.05, and 0.1) and (La 0.8 Ca 0.2−x Sr x )CrO 3 (x = 0.2) were found to have orthorhombic and rhombohedral symmetries, respectively. Relative density of the (La 0.8 Sr 0.2 )CrO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 8 publications
1
8
1
Order By: Relevance
“…The densification of La 0.85 Sr 0.15−x Ca x CrO 3 was studied for values of x = 0, 0.05 and 0.1 as a function of temperatures. The substitution of Ca for Sr in La 0.85 Sr 0.15−x Ca x CrO 3 enhanced the sinterability over La 0.85 Sr 0.15 CrO 3 sample, which is consistent with that of Kim et al[6]. They suggested that partial replacement of Sr atoms by Ca might lower SrO activity.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The densification of La 0.85 Sr 0.15−x Ca x CrO 3 was studied for values of x = 0, 0.05 and 0.1 as a function of temperatures. The substitution of Ca for Sr in La 0.85 Sr 0.15−x Ca x CrO 3 enhanced the sinterability over La 0.85 Sr 0.15 CrO 3 sample, which is consistent with that of Kim et al[6]. They suggested that partial replacement of Sr atoms by Ca might lower SrO activity.…”
supporting
confidence: 90%
“…Ding et al [5] have reported that La 0.85 Sr 0.15 CrO 3 showed linear thermal expansion behavior and its TEC value was very close to that of 8 mol.%-Y 2 O 3 -stabilized-ZrO 2 (8YSZ) electrolyte, while it suffered from poor sinterability in air. Kim et al [6] have found that the (La 1−x Sr x )CrO 3 must be sintered at relative high temperatures and that the (La 1−x Ca x )CrO 3 perovskite showed better sinterability and solubility in comparison with the phase (La 1−x Sr x )CrO 3 , but * Corresponding author. Tel.…”
Section: Introductionmentioning
confidence: 99%
“…XRD patterns of (La 0.8 Ca 0.2 )(Cr 0.9-x Co 0.1 Ni x )O 3-d specimens sintered at 1500 C for 6 h. TABLE I. Lattice parameters, cell volumes, crystal symmetries, and tolerance factor of La 0.8 Ca 0.2 Cr 0.9-x Co 0.1 Ni x O 3-d specimens sintered at 1500 C for 4 h. Composition Lattice parameter (Å ) Cell volume (Å 3 ) Crystal symmetries Tolerance factor x = 0.03 a = 5.440(1), b = 5.664(2), c = 7.762(6) 239.12 Orthorhombic 0.8000 x = 0.06 a = 5.444(2), b = 5.636(4), c = 7.736(5) 237.24 Orthorhombic 0.8008 x = 0.09 a = 5.449(1), b = 5.452(3), c = 7.699(Cr 0.9-x Co 0.1 Ni x )O 3-d specimens. These values are much larger than 20 S/cm of the (La 0.8 Ca 0.2 )CrO 3 specimen as observed by Kim et al,26 which was synthesized by the Pechini process. This indicated that cobalt and nickel elements substituted for (La 0.8 Ca 0.2 )CrO 3 in Cr sites can significantly improve its electrical conductivity.…”
mentioning
confidence: 55%
“…The Arrhenius plot for the electrical conductivity in air of Mn doping on (La 0.8 Ca 0.2 )(Cr 0.9 Co 0.1 )O 3Àd specimens is plotted in Fig. These values are much larger than the 20 S/cm for the (La 0.8 Ca 0.2 )CrO 3 specimen observed by Kim et al 19 which was synthesized by the Pechini process. The linearity can be found between ln (rT) vs 1/T for all specimens.…”
Section: Compositionmentioning
confidence: 77%